Komunikacja niewerbalna Koreańczyków na tle tradycji kulturowej. Perspektywa glottodydaktyczna - Janicka, Izabela (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2009)
The article deals with the question of teaching a nonverbal code in the foreign language learning process of students coming from Korea. The social principles of Confucian philosophy, generally recognized in the Far East, provide an important context explaining the problems of interference in nonverbal communication and of achieving cultural competence. Several types of nonverbal messages have been presented, with focus on the gestures—inadequate for the Polish cultural code—used by Koreans in communicative situations. It has been stressed that such aspects of the language must be considered in teaching Polish in order for students to achieve sociocultural competence parallely to linguistic competence. In the face of worldwide promotion of the Polish language, the inclusion of nonverbal communication and cultural realities should play a bigger role in the teaching programs and be seen as important, although often omitted elements.